Pengaruh Metode Mind Mapping dan Motivasi Terhadap Hasil Belajar Sejarah Kebudayaan Islam Siswa Kelas XI MAN 3 Banyuwangi - Al-Afghani, Shalahuddin; Mahfud, Ali; Asari, Anang (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) STIB Banyuwangi, 2023)
The history of Islamic culture is an important aspect for a Muslim to know how Islam can develop until now, and how students can understand the history of Islamic culture which is very much in a short time, namely by using the mind mapping learning method. This study aims to 1) test and analyze the effect of the mind mapping method on the learning outcomes of Islamic cultural history 2) to test and analyze the effect of motivation on the learning outcomes of Islamic cultural history 3) to test and analyze the effect of the mind mapping method of motivation simultaneously on the learning outcomes of Islamic cultural history. These three objectives were studied in class XI students of MAN 3 Banyuwangi. In this study, the researcher used a quantitative method and the results of this study were 1) the mind mapping method had an effect on the learning outcomes of Islamic cultural history 2) motivation affected the learning outcomes of Islamic cultural history 3) the mind mapping method of motivation simultaneously on the learning outcomes of Islamic cultural history